2003
DOI: 10.1046/j.1468-1331.2003.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis in children: clinical features and HLA‐DR linkage

Abstract: This study includes 90 children (41 female and 49 male) in the age range of 2-16 years with acute disseminated encephalomyelitis (ADEM). Thirty-three patients developed ADEM following rubella infection, 26 children following varicella infection, 20 suspected viral aetiology ADEM and 11 multiphasic disseminated encephalomyelitis (MDEM). All patients had neurological, routine laboratory and viral serology study with an enzyme-linked immunosorbent assay. Brain and/or spinal cord magnetic resonance imaging (MRI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 12 publications
2
38
0
2
Order By: Relevance
“…The HLA DQB1*0602 allele confers genetic susceptibility to Brazilian MS patients from Rio de Janeiro City (RJC), independently of the genetic background [21][22][23] . The presence of a common allele conferring genetic susceptibility for both MS and ADEM in the same population was found by Idrissovaet al 20 among Russian MS and ADEM patients. In the present study, we found the HLA DQB1*0602 and HLA DRB1*1501 alleles sharing genetic susceptibility to MS and ADEM in patients from RJC.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The HLA DQB1*0602 allele confers genetic susceptibility to Brazilian MS patients from Rio de Janeiro City (RJC), independently of the genetic background [21][22][23] . The presence of a common allele conferring genetic susceptibility for both MS and ADEM in the same population was found by Idrissovaet al 20 among Russian MS and ADEM patients. In the present study, we found the HLA DQB1*0602 and HLA DRB1*1501 alleles sharing genetic susceptibility to MS and ADEM in patients from RJC.…”
Section: Discussionsupporting
confidence: 61%
“…The significantly association of ADEM patients with HLA DRB1*1501 allele can speculate about a protector role of these allele among the monophasic course and rapid improvement of those patients. Accordingly to this point of view, Idrissovaet al 20 also found association of HLA DRB1*01 allele with ADEM susceptibility in Russian patients. And like DRB1*1501, DRB1*01 has been described as an allele associated to low morbidity in MS patients.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations